Krrish 3 [videorecording (DVD)] - Roshan, Rakesh; Roshan, Hrithik; Oberoi, Vivek, 1976-; Chopra Jonas, Priyanka; Ranaut, Kangana (Eros International, 2013)
Each time evil awakens in the world, a superhero rekindles his superpowers. This time Krrish is back, with thrice the power to destroy the demonic Kaal and his bastion of beastly mutants.